A Review Study on Sulfate-Radical-Based Advanced Oxidation Processes for Domestic/Industrial Wastewater Treatment: Degradation, Efficiency, and Mechanism - Xia, Xinhui; Zhu, Fengyi; Li, Jianju; Yang, Haizhou; Wei, Liangliang; Li, Qiaoyang; Jiang, Junqiu; Zhang, Guangshan; Zhao, Qingliang (Frontiers in Chemistry, 2020)
High levels of toxic organic pollutants commonly detected during domestic/industrial wastewater treatment have been attracting research attention globally because they seriously threaten human health. Sulfate-radical-based advanced oxidation processes (SR-AOPs) have been successfully used in wastewater treatment, such as that containing antibiotics, pesticides, persistent organic pollutants, for refractory contaminant degradation. This review summarizes activation methods, including physical, chemical, and other coupling approaches, for efficient generation of sulfate radicals and evaluates their applications and economic feasibility. The degradation behavior as well as the efficiency of the generated sulfate radicals of typical domestic and industrial wastewater treatment are investigated. The categories and characteristics of the intermediates are also evaluated. The role of sulfate radicals, kinetic characteristics, and possible mechanisms for organic elimination are assessed. In the last section, current difficulties and future perspectives of SR-AOPs for wastewater treatment are summarized.